Comparison of Coronary Angiography Characteristics among Acute Coronary Syndrome Patients in Young and Old Age Patients at Cipto Mangunkusumo Hospital Jakarta - Rahmad Isnanta; Marulam M Panggabean; Idrus Alwi (Acta Medica Indonesiana, 2016)
Aim: to identify the difference between coronary angiography in patients with acute coronary syndrome (ACS) aged ≤45 years and those aged >45 years. Methods: a total of 322 ACS patients who underwent coronary angiography in ICCU of Cipto Mangunkusumo Hospital, Jakarta between January 2008 and December 2012 were included in this study. The severity of coronary stenosis was determined by vessel score and coronary score. A significant vessel score was defined as a stenosis of coronary vessel of >70%. Patients were divided into two groups: those aged ≤45 years (72 cases) and those aged >45 years (250 cases). The statistical analysis was performed with Chi-square test for categorical data with two-unpaired groups and the t-test or Mann-Whitney for numerical data. Results: the highest distribution of 1-VD (single-vessel disease) patients was found the group of patients aged ≤45 years (43.1% vs 26.0%); while for 3-VD (triple-vessel disease) patients, the highest distribution was noticed in the group of patients aged >45 years (31.6% vs 18.1%). The stenosis score was lower in patients aged ≤45 years compared those aged >45 years (median stenosis score 4 vs 8), p<0.001. Atherosclerosis was found most common for the left anterior descending artery in both age groups (65.3% and 74.0%). However, there was less significant stenosis lesion for the Left Circumflex and Right Coronary Arteries in patients aged ≤45. The result was statistically significant (26.4% and 31.9% vs 46.4% and 57.2%, p=0.002 and 0.001). Conclusion: the number of coronary artery diseases (vessel score) and stenosis score is lower in patients aged ≤45 years compared to patients aged >45 years.